The Foreign Fairy-Tales Translated in Armenian in the Personal Library of Hovhannes Tumanyan - Yeghiazaryan, Ani (Bulletin of Yerevan University B: Philology, 2022)
The article refers for the first time to a number of fairy tales translated into Armenian at the end of the 19th and the beginning of the 20th century, the printed copies of which are kept in the personal library of Hovhannes Toumanian.A significant part of the poet's rich and multi-content library is preserved and studied in the Yerevan Hovhannes Toumanian Museum. Toumanian was well-acquainted with the folkloric culture of different nationalities, especially the genre of fairy tales. Throughout his creative life he attached special importance to their Armenian translations, the tasteful provision of illustrations and quality printing. According to Toumanian: "Fairy tales are abysses: deep, endless... A fairy tale is the highest creation, even geniuses cannot create a fairy tale".Referring in the article to the fairy tales translated into Armenian in Tօumanian's library, as well as those published in the "Hasker" children's magazine at that time, it becomes possible to get a partial idea of ​​some contributions of Armenian translated literature of the beginning of the 20th century, the layer of interests, to make visible the environment where Hovhannes Toumanian made his translations.
Keywords: Toumanian; fairy tale; translation; foreign; library; history; child; illustration; collection; reader; museum